UPAYA MENGEFEKTIFKAN TEKNIK PRAKTIS PEMBUATAN POLA DENGAN METODE PICTURE AND PICTURE PADA SMK NEGERI 3 BANDA ACEH - Ida Rusmalanur (Visipena, 2015)
The objectives to be achieved in this research is to improve the skills of students in the learning process, especially on the subject of making a woman's basic pattern. In this study, the authors deliberately taking picture and picture method to make it easier for students to understand because the old method is difficult for students to understand.With this method, students are expected to be motivated learning process can run with what was expected, the method of picture and picture also shows the phases of archetypal images and completeness of stationery and other support.